Implementation of Rahn Contract Principles in Sharia Pawnshops to Enhance Public Interest in Sharia Pawn Services - Putra, Hafiza; Azzaki , Muhammad Adnan; Deli, Mazzlida Mat (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
An Islamic financial institution is a business entity whose activities are in the field of Islamic finance and its assets are in the form of financial and non-financial based on Islamic sharia principles, one of which is a sharia pawnshop (rahn). A rahn contract is a contract for the delivery of goods as collateral for a debt transaction that is agreed upon within a certain period of time. The lack of public knowledge of the principles of sharia pawnshops has led to the need for efforts to increase literacy to increase public interest in Islamic financial institutions. The purpose of this research is to provide information and understanding about the principles of the Rahn contract for Sharia pawnshops.